2016
DOI: 10.1080/24748668.2016.11868926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a specific concurrent water and dry-land training over a season in young swimmers’ performance

Abstract: The aims of this study were to assess over a full season: (i) the effect of a combined dry-land strength and conditioning and in-water program on the swimming performance of young swimmers; (ii) the effect of such program on the performance determinants; (iii) the effect of the training periodization designed. A longitudinal research design assessing an agegroup of young swimmers over a season was carried out. Methods: Twentyseven young swimmers (12 boys: 13.55±0.72-y; 15 girls: 13.16±0.93-y; both sexes in Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The effect of resistance training on dry land or in-water on kinematic variables (velocity (v), stroke rate (SR), stroke length (SL) and stroke index (SI)) was studied in several investigations [ 6 , 7 , 9 , 17 ]. Morais et al [ 17 ] showed that 34 weeks of a training program included dry land resistance (upper and lower strength) and improved the SR (4.88%) and V (3.60%) in the 100-m front crawl in competitive swimmers (age = 13.3 ± 0.85 years). More recently, Lopes et al [ 7 ] revealed that 8 weeks of dry land included BP and MBT and did not change the SL and SI in the 50-m front crawl ( p > 0.05) in competitive swimmers.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of resistance training on dry land or in-water on kinematic variables (velocity (v), stroke rate (SR), stroke length (SL) and stroke index (SI)) was studied in several investigations [ 6 , 7 , 9 , 17 ]. Morais et al [ 17 ] showed that 34 weeks of a training program included dry land resistance (upper and lower strength) and improved the SR (4.88%) and V (3.60%) in the 100-m front crawl in competitive swimmers (age = 13.3 ± 0.85 years). More recently, Lopes et al [ 7 ] revealed that 8 weeks of dry land included BP and MBT and did not change the SL and SI in the 50-m front crawl ( p > 0.05) in competitive swimmers.…”
Section: Introductionmentioning
confidence: 99%
“…Elite swimmers exhibited superior lower-limb S&P for the swimming turn compared to younger and less experienced swimmers (Jones et al, 2018). A cluster analysis of young swimmers over a full season noted that the cluster of best performers (talented swimmers) was always characterised by parameters related to dry-land S&P, but not in the cluster of mid-tier swimmers (proficient swimmers) and low-tier counterparts (non-proficient swimmers) (Morais et al, 2016a). Strong correlations (R = 0.93) have been reported between upper body muscular strength and swimming performance (Smith, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Besides, the findings showed that improved jumping ability increased the vertical force components of on the grab, track and swing starts in swimming. According to the other study, Morais et al [28] stated that the swimmers with higher body dimensions achieved better performances in the squat jump, countermovement jump, throwing velocity tests. Amaro et al…”
Section: Discussionmentioning
confidence: 94%